2015
DOI: 10.1080/02701367.2015.1053104
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Concurrent Training on Running Performance Over 6 Days

Abstract: Combining strength training on alternating days with endurance training on consecutive days impairs MVC and running performance at maximal effort and increases RMS and RMF over 6 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Studies have reported high levels of EIMD with concomitant impairments in running economy [15][16][17], running time-trial performance [18], and cycling performance [19] for several days following a bout of resistance exercises. These findings suggest that a bout of RT may impair the quality of subsequent endurance training sessions as a result of EIMD symptoms [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported high levels of EIMD with concomitant impairments in running economy [15][16][17], running time-trial performance [18], and cycling performance [19] for several days following a bout of resistance exercises. These findings suggest that a bout of RT may impair the quality of subsequent endurance training sessions as a result of EIMD symptoms [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ratings of muscle soreness and fatigue were obtained following the completion of three repetitions of body weight squats. The muscle soreness and fatigue rating method used in this study was a standard 1–100 visual analogue scale adapted from a previous study ( Doma & Deakin, 2015 ). Specifically, 1–100 indicated “not very sore at all” to “very sore,” respectively, for the rating of muscle soreness and 1–100 indicated “not fatigued at all” to “very fatigued,” respectively, for the rating of muscle fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…This approach does not replicate real-world resistance training (RT) practices involving isoinertial, concentric and eccentric, multi-articular contractions with heavy external loads. More recently, studies have reported that lower body RT sessions, such as squats, leg press, leg extension and leg curls, produced symptoms of EIMD [8], and as a result, impaired RE measures and maximal effort running performance for 24–48 h post-exercise [911]. However, these studies examined running performance measures in thermo-neutral conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies examined running performance measures in thermo-neutral conditions. As athletes experience greater thermal strain in hot and humid conditions [12, 13], and the symptoms of EIMD increases physiological cost during exercise at a given workload [11, 14], running during periods of EIMD in the heat may further augment thermal strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation